Preliminary observations on the development of a latex, slide agglutination test and its use for serodiagnosis of heartwater (Cowdria ruminantium infection) in small ruminants - Kakaire, M.N.; Shompole, S.; Ngatia, T.A.; Musoke, A.J.; Munyua, W.K. (1998)
The possibility of detecting Cowdria ruminantium antibodies and antigen in sera and plasma of experimentally infected goats, using latex beads coated with crude Cowdria antigen (latex slide agglutination antibody test) and latex beads coated with rabbit anti-Major antigenic protein-2 (aMAP2) serum (latex slide agglutination antigen test) was investigated. In the Latex slide agglutination antibody test, Cowdria antibodies were detected in sera of goats which suffered a non fatal disease, but not in sera of goats which suffered an acute and fatal disease. Out of 81 field goat sera tested, 19(23.4 percent) were positive, 11(13.6 percent) weak positive (border line) and 51 (63 percent) negative. The Latex slide agglutination antigen test was unable to detect Cowdria antigen in blood of the infected goats. However, when solubilized elementary bodies (EBs) and intact EBs were tested using the Latex slide agglutination antigen test, weak agglutination was observed with the solubilized EBs and there was no agglutination observed with the intact EBs. The present study has demonstrated that the Latex slide agglutination test, if improved, has the potential of being a useful tool for routine diagnosis of heartwater in the field.